Internetnutzer und Korruptionswahrnehmung: Eine ökonometrische Untersuchung - Carsten Gerrits (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2013)
The current work focuses on the economics of corruption, with an emphasis on the influence of internet users and press freedom on the perception of corruption. An analysis of crosssectional data obtained for 113 countries in 2010 was implemented by means of a generalized linear model involving a gamma-distributed dependend variable (Gamma-GLM), which is known to be superior to the frequently used weighted least square-method. Results revealed that both determinants, i.e. internet use, and press freedom, have isolated and economically significant effects on the way corruption is perceived. In particular, internet users seem to shape the perception, as reflected in an effect which was two times larger than the effect of press freedom. While the impact of these factors on the true corruption remains to be explored in detail, their influence on corruption perception could be identified as nonlinear.
Keywords: C46; C21; D73; H83; 330; corruption perception; internet; press freedom; generalized linear model; Gamma-GLM